The role of Nox1 and Nox2 in GPVI-dependent platelet activation and thrombus formation() - Walsh, T.G. (Elsevier, 2014)
BACKGROUND: Activation of the platelet-specific collagen receptor, glycoprotein (GP) VI, induces intracellular reactive oxygen species (ROS) production; however the relevance of ROS to GPVI-mediated platelet responses remains unclear. OBJECTIVE: The objective of this study was to explore the role of the ROS-producing NADPH oxidase (Nox)1 and 2 complexes in GPVI-dependent platelet activation and collagen-induced thrombus formation. METHODS AND RESULTS: ROS production was measured by quantitating changes in the oxidation-sensitive dye, H(2)DCF-DA, following platelet activation with the GPVI-specific agonist, collagen related peptide (CRP). Using a pharmacological inhibitor specific for Nox1, 2-acetylphenothiazine (ML171), and Nox2 deficient mice, we show that Nox1 is the key Nox homolog regulating GPVI-dependent ROS production. Nox1, but not Nox2, was essential for CRP-dependent thromboxane (Tx)A(2) production, which was mediated in part through p38 MAPK signaling; while neither Nox1 nor Nox2 was significantly involved in regulating CRP-induced platelet aggregation/integrin α(IIb)β(3) activation, platelet spreading, or dense granule and α-granule release (ATP release and P-selectin surface expression, respectively). Ex-vivo perfusion analysis of mouse whole blood revealed that both Nox1 and Nox2 were involved in collagen-mediated thrombus formation at arterial shear. CONCLUSION: Together these results demonstrate a novel role for Nox1 in regulating GPVI-induced ROS production, which is essential for optimal p38 activation and subsequent TxA(2) production, providing an explanation for reduced thrombus formation following Nox1 inhibition.